MAPPING DIGITAL TRANSFORMATION IN RURAL BANKING, A KOTTER BASED ROADMAP OF PT BPR - Asih Endah Subandiyah; Andri Purnamawati; Eny Sulistyowati (Nusantara Hasana Journal, 2026)
This study examines the strategic digital transformation of PT BPR BDE over a five-year period (2020–2024) through a structured roadmap analysis aligned with Kotter’s 8-Step Change Model. Positioned within the context of rural banking in Indonesia, the research utilizes content analysis of institutional documents, promotional materials, and regulatory frameworks to map organizational change year-by-year. Findings reveal that transformation is not solely driven by technological deployment, but by internal readiness, leadership commitment, communicative strategies, and regulatory compliance. The integration of Kotter’s framework with behavioral adoption theory (UTAUT2) and qualitative content interpretation (Krippendorff) offers a robust methodological model for evaluating digitalization in microfinance settings. PT BPR BDE’s approach demonstrates how strategic alignment and digital storytelling can institutionalize cultural change and enhance stakeholder engagement. This study contributes both theoretically and practically to strategic change management discourse in resource-constrained financial institutions.